IMPROVE STUDENTS' MATHEMATICAL CRITICAL THINKING SKILLS SUMATERA UTARA ISLAM: USING MODELS FOR PROBLEM-BASED LEARNING - Syahlan Syahlan; Rianita Simamora (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
This study's objective was to determine the effects of the problem-based learning model on students enrolled in the mathematics education program at the Islamic University of North Sumatra while they studied to improve their critical thinking skills. This type of quasi-experimental study aims to determine how the participant's parameters are affected by the treatment. "One-group pretest-posttest design" is the name of the study's approach. The research was carried out there with the participation of 35 students from the Mathematics Study Program at the Islamic University of North Sumatra. In this study, data were collected through tests and observations. A tool for data analysis is the t-test. A computer application named SPSS version 25.0 is used to process statistical data. According to the results, using the PBL learning model has an impact on students' mathematical critical thinking skills at the Islamic University of North Sumatra's Mathematics Education Study Program. The t-test significance value of 0.0001, which is less than 0.05, supports this.